Psychrotrophic bacteria in milk: How much do we really know? - de Oliveira, Gislene B. (Braz J Microbiol, 2015)
The occurrence of psychrotrophic bacteria in raw milk is studied worldwide due to the difficulties associated with controlling their growth during cold storage and the consequent negative effects upon fluid milk or dairy products. Among the psychrotrophic bacteria, the genus Pseudomonas (represented primarily by P. fluorescens) has been highlighted as the cause of numerous defects in dairy products. In light of its perceived predominance, this species has frequently been chosen as a model organism to assess the effects of psychrotrophic bacteria on milk or to evaluate the efficacy of control measures. However, recent findings derived from the application of molecular biological techniques have exposed a number of deficiencies in our knowledge of the biology of milk-associated psychrotrophs. Furthermore, it has been revealed that microbe to microbe communication plays a significant role in determining both the identities and the extent to which different groups of microbes develop during cold storage. The application of molecular identification methods has exposed errors in the classification of members of the genus Pseudomonas isolated from cold stored milk and has stimulated a reevaluation of the presumed status of P. fluorescens as the predominant milk-associated psychrotrophic species. This article presents a succinct review of data from studies on psychrotrophic bacteria in milk, some of which contest established theories in relation to the microbiology of cold stored raw milk, and poses the question: how much do we really know?